Characterization of the chained form with delays. Issue 18 (2016) - Li, S.; Califano, C.; Moog, C-H.
Abstract: The chained form with time-delays is introduced and it generalizes the classical chained form which is encountered in mobile robotics with non holonomic constraints. A full characterization for the two-input nonlinear time-delays systems that are equivalent to the chained form with delays is derived and necessary and sufficient conditions are given.